2017
DOI: 10.1038/s41598-017-06932-3
|View full text |Cite
|
Sign up to set email alerts
|

ApoE Influences the Blood-Brain Barrier Through the NF-κB/MMP-9 Pathway After Traumatic Brain Injury

Abstract: Apolipoprotein E (ApoE), encoded by the ApoE gene (APOE), influences the outcomes of traumatic brain injury (TBI), but the mechanism remains unclear. The present study aimed to investigate the effects of different ApoEs on the outcome of TBI and to explore the possible mechanisms. Controlled cortical impact (CCI) was performed on APOEε3 (E3) and APOEε4 (E4) transgenic mice, APOE-KO (KO) mice, and wild type (WT) mice to construct an in vivo TBI model. Neurological deficits, blood brain barrier (BBB) permeabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 29 publications
(32 reference statements)
3
50
0
1
Order By: Relevance
“…These results suggest that endogenous apoE plays a vital role in the integrity of the BSCB after SCI. Our results are consistent with previous studies showing that apoE deficiency increases the permeability of blood-brain-barrier (BBB) in vivo and in vitro (Bell et al, 2012; Nishitsuji et al, 2011; Fullerton et al, 2001; Hafezi-Moghadam et al, 2007; Teng et al, 2017). For example, apoE −/− mice have been shown to increase BBB integrity damage in many animal models, such as brain injury (Methia et al, 2001; Teng et al, 2017), hyperlipidemia, and/or atherosclerosis, and aged mice (Grinberg and Thal, 2010; Badaut et al, 2012).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results suggest that endogenous apoE plays a vital role in the integrity of the BSCB after SCI. Our results are consistent with previous studies showing that apoE deficiency increases the permeability of blood-brain-barrier (BBB) in vivo and in vitro (Bell et al, 2012; Nishitsuji et al, 2011; Fullerton et al, 2001; Hafezi-Moghadam et al, 2007; Teng et al, 2017). For example, apoE −/− mice have been shown to increase BBB integrity damage in many animal models, such as brain injury (Methia et al, 2001; Teng et al, 2017), hyperlipidemia, and/or atherosclerosis, and aged mice (Grinberg and Thal, 2010; Badaut et al, 2012).…”
Section: Discussionsupporting
confidence: 93%
“…Our results are consistent with previous studies showing that apoE deficiency increases the permeability of blood-brain-barrier (BBB) in vivo and in vitro (Bell et al, 2012; Nishitsuji et al, 2011; Fullerton et al, 2001; Hafezi-Moghadam et al, 2007; Teng et al, 2017). For example, apoE −/− mice have been shown to increase BBB integrity damage in many animal models, such as brain injury (Methia et al, 2001; Teng et al, 2017), hyperlipidemia, and/or atherosclerosis, and aged mice (Grinberg and Thal, 2010; Badaut et al, 2012). Since BSCB plays an important role in maintaining the microenvironment and normal functions of the spinal cord, disruption of BSCB caused by SCI leads to the leakage of blood constituents, such as inflammation cells, immune proteins and other large molecules, which collectively initiate and/or contribute to a “vicious cycle” of pathophysiological processes, resulting in progressive tissue loss and neurological deficits after injury (Popovich et al, 1996; Whetstone et al, 2003).…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, individuals carrying the APOE4 gene in Alzheimer’s Disease display accelerated pericyte degeneration [ 22 ]. A recent experimental TBI paper also found that whole cortex homogenates from APOE4 mice have reduced tight protein compared to APOE3 mice at 7 days post-injury, alongside increased MMP-9 activity [ 76 ]. Our results show that at 10 days post-injury, closure of the BBB has occurred in APOE3 mice.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, APOE tends to maintain BBB integrity and promote neurological recovery. While APOE-deficiency provokes BBB dysfunction, exogenously administered APOE or its mimetic peptides preserve BBB integrity in experimental studies [197][198][199][200][201][202][203].…”
Section: The Bbb Integrity-promoting Effects Of Astrocytesmentioning
confidence: 99%